Addressing the Geriatric Hypertension Crisis in the Philippines: Challenges and Strategies for Improved Care - Anonuevo, James Luke Abalos (Magyar Gerontológia, 2024)
This paper provides an in-depth analysis of the challenges confronting the elderly population in the Philippines, focusing on economic insecurity, healthcare accessibility, social isolation, and the socio-cultural context of aging. While the elderly population remains smaller in proportion compared to other Southeast Asian nations—growing from 2.7% in 1990 to a projected 7.7% by 2025—this demographic shift brings significant implications. The increase in the aged dependency ratio, expected to double from 5.5 elderly per 100 working-age persons in 1990 to 10.5 by 2025, reflects the pressures on younger generations to support an aging population.